The cross-sectional study on changes in fasting lipid profile and liver enzyme in type 2 diabetic patients in tertiary healthcare - Desai, Paras; Rathod, Sanket; Bhavsar, Hitendrakumar K.; Prajapati, Bhavik; Patel, Sachin; Kaliya, Mehul (International Journal of Research in Medical Sciences, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is associated with metabolic dysfunctions, including Dyslipidemia and liver enzyme abnormalities. Elevated fasting lipid profiles and liver enzymes have been linked to poor glycaemic control, increasing the risk of cardiovascular disease and non-alcoholic fatty liver disease (NAFLD). This study aims to investigate the correlation between glycaemic status, lipid abnormalities, and liver enzyme alterations in T2DM patients. Methods: A cross-sectional observational study was conducted at Dr. M.K. Shah Medical College & Research Centre and Smt. S.M.S. Multispecialty Hospital, Ahmedabad. A total of 125 T2DM patients were enrolled based on ADA guidelines. Demographic data, glycaemic parameters (FBS, PPBS, HbA1c), fasting lipid profile, and liver function tests (SGOT, SGPT) were analyzed. Data were statistically assessed using SPSS version 20, with a p value <0.05 considered significant. Results: A significant association was observed between poor glycaemic control (HbA1c>10%) and elevated liver enzymes, with a fivefold increase in SGOT and SGPT levels (p<0.05). Dyslipidemia was highly prevalent, with increased triglycerides and LDL levels strongly correlating with worsening glycaemic status. HDL levels showed no significant association. Conclusions: The findings emphasize the importance of monitoring liver function and lipid profiles in T2DM patients to prevent complications such as NAFLD and cardiovascular disease. Early detection of metabolic abnormalities can aid in risk stratification and targeted therapeutic interventions for better diabetes management.